Covariance and specificity in adolescent schizotypal and borderline trait expression. Issue 5 (16th January 2014) - Badoud, Deborah; Billieux, Joël; Eliez, Stephan; Imhof, Anouk; Heller, Patrick; Eytan, Ariel; Debbané, Martin
Abstract: Aims: The first aim of the present study is to assess the overlap between borderline and schizotypal traits during adolescence. The second objective is to examine whether some psychological factors (i.e. cognitive coping mechanisms, impulsivity and encoding style) are differentially related to borderline and schizotypal traits and may therefore improve the efficiency of clinical assessments. Methods: One hundred nineteen community adolescents (57 male) aged from 12 to 19 years completed a set of questionnaires evaluating the expression of borderline and schizotypal traits as well as cognitive emotion regulation (CER), impulsivity and encoding style. Results: Our data first yielded a strong correlation between borderline and schizotypal scores ( r = 0.70, P < 0.001). Secondly, linear regression models indicated that the 'catastrophizing' CER strategy and the 'lack of premeditation' impulsivity facet accounted for the level of borderline traits, whereas an internal encoding style predominantly explained schizotypal traits. Conclusions: Our results support the abundant literature showing that borderline and schizotypal traits frequently co‐occur. Moreover, we provide original data indicating that borderline and schizotypal traits during adolescence are linked to different specific psychological mechanisms. Thus, we underline the importance of considering these mechanisms in clinical assessments, in particular to help disentangle personality disorder traits in youths.